Clinicodemographic Profile of Adult Patients With Chronic Urticaria in an Allergy Specialty Clinic: A Five-Year Review (2019 to 2023) - Geraldez, Maria Francesca Emily; Kwong-Buizon, Shirley (Philippine Journal of Allergy, Asthma and Immunology, 2024)
Background: There is variability among the prevalence and characteristics of chronic urticaria. Objectives: This study aimed to determine clinicodemographic characteristics of adult patients diagnosed with chronic urticaria in an allergy clinic in Metro Manila, Philippines, from 2019 to 2023. Methodology: A cross-sectional review of medical records from patients aged 19 and above at an allergy clinic in Metro Manila was conducted from 2019 to 2023. Clinicodemographic features, along with their frequencies and percentages, were obtained. Results: Seventy-five patients with chronic urticaria were investigated. The majority were women (72%) aged 30 to 39 (30.7%) from the National Capital Region (85.3%). Most were married (36%), college graduates (30.7%), and employed (54.7%), with 62.7% seeking their initial consultation 2 to 12 months after the onset of the disease. Fifty-seven percent of patients had a personal history of atopy and 54.7% had a family history of atopy. Thirty-seven percent of patients had comorbidities, with hypertension as the most frequent (18.7%). Thirty-three percent of patients were suspected with chronic inducible urticaria with dermographism as the most common suspected trigger (21.3%). Fifty-eight percent of patients had urticaria before COVID-19 vaccination, while 42% had a previous history of COVID-19 vaccine before the onset of symptoms. However, no further tests were done to confirm its association with the disease. Fifteen patients underwent skin prick tests, and all demonstrated positive skin test reactivity to some form of aeroallergen or food allergens. All patients were given second-generation H1-antihistamine at varying doses. The majority of patients (65.3%) reported an improvement in symptoms. Only 26.7% of patients used the 7-day Urticaria Activity Score, while 29.3% used the Urticaria Control Test to monitor their symptoms. Conclusion: The prevalence of chronic urticaria (13%) was higher than the global estimate of 1%. Most chronic urticaria patients were female, aged 30 to 39, married, college graduates, and employed who showed symptoms within 2 to 12 months after the onset of the disease. Approximately 50% of them had a personal and family history of atopy. Most patients do not have comorbidities and suspected inducible triggers. All patients who underwent skin prick tests showed reactivity to some allergens (aeroallergens, food allergens). All patients were given second-generation H1-antihistamines at varying doses. Many patients experienced symptom improvement with the prescribed medications despite poor compliance with the recommended monitoring tools. According to clinical history, the onset of chronic urticaria was not attributed to COVID-19 vaccination in most cases.